Lastentarhatyö, kansanopetuksen osa ja kotikasvatuksen tuki:toiminnan päämäärät ja toteutuminen Pohjois-Suomessa 1800-luvun lopulta vuoteen 1938 - Lujala, E. (Elise) (University of Oulu, 2007)
Abstract Kindergartens were established as part of the educational system in the period of autonomy under Russia, but they were subjected to social administration soon after independence. The causes of this decision and its consequences on the development of kindergarten work have been considered in various contexts. The current study aims to establish the kind of pedagogical frame of reference that the Finnish kindergarten institution was associated with in its early decades, how the administration of kindergarten work developed and how these approaches were reflected in the emergence of the first northern Finnish kindergartens by 1938. The theoretical frame of reference for my discussion is formed by the kindergarten philosophy based on Central European roots that was applied in Finland after the mid-19th century. The basis for this approach implemented in different forms was provided by kindergarten activities based on the views of Friedrich Fröbel (1782–1852). The goal has been to make visible the early times of local kindergartens, the main phases of change in the development of central administration, and the impact of administrative measures on municipal decisions in promoting, supporting and even restricting them. The most common growth factor in northern Finnish towns was the increase in industry and trade, with improved traffic communication as an essential prerequisite. Crowded living conditions of the industrial population in the suburban areas, the fact that both of the parents were working, and long working days made the living conditions of smallest children in particular insecure and unfavourable for growth. Meanwhile the northern border towns wanted opportunities for physical exercise and various activities for children to counterbalance the licentcious life on the streets and the bad influences arising from it. Due to a limitation of resources, the changes in this sector of administration in the early years of national independence did not meet the requirements set for kindergarten work. The ...